In situ Raman spectroscopy study on the effect of antioxidants on high temperature oxidation properties of TMPTO. Issue 5 (19th July 2019) - Cheng, Bingxue; Duan, Haitao; Jin, Yongliang; Wei, Lei; Dan, Jia; Chen, Song; Li, Jian
Abstract : Purpose: This paper aims to investigate the thermal oxidation characteristics of the unsaturated bonds (C=C) of trimethylolpropane trioleate (TMPTO) and to reveal the high temperature oxidation decay mechanism of unsaturated esters and the nature of the anti-oxidation properties of the additives. Design/methodology/approach: Using a DXR laser microscopic Raman spectrometer and Linkam FTIR600 temperature control platform, the isothermal oxidation experiments of TMPTO with or without 1.0 wt. % of different antioxidants were performed. Findings: The results indicated that the Raman peaks of =C-H, C=C and -CH2 - weaken gradually with prolonged oxidation time, and the corresponding Raman intensities drop rapidly at higher temperatures. The aromatic amine antioxidant can decrease the attenuation of peak intensity, as it significantly reduces the rate constant of C=C thermal oxidation. The hindered phenolic antioxidant has a protective effect during the early stages of oxidation (induction period), but it may accelerate the oxidation of C=C afterwards. Originality/value: Research on the structure changes of synthetic esters during oxidation by Raman spectroscopy will be of great importance in promoting the use of Raman spectroscopy to analyze the oxidation of lubricants.